2019
DOI: 10.1063/1.5128696
|View full text |Cite
|
Sign up to set email alerts
|

Calcium response in bone cells at different osteogenic stages under unidirectional or oscillatory flow

Abstract: Human stroma and epithelium co-culture in a microfluidic model of a human prostate gland Biomicrofluidics 13, 064116 (2019);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Intracellular calcium is a second messenger in cells, and it plays an important role in osteogenesis [ 34 , 35 ]. Studies have shown that the concentration of intracellular calcium ion is positively associated with adhesion, migration, proliferation, and differentiation in MC3T3-E1 cells via modulation of a large variety of intracellular downstream signal targets.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular calcium is a second messenger in cells, and it plays an important role in osteogenesis [ 34 , 35 ]. Studies have shown that the concentration of intracellular calcium ion is positively associated with adhesion, migration, proliferation, and differentiation in MC3T3-E1 cells via modulation of a large variety of intracellular downstream signal targets.…”
Section: Discussionmentioning
confidence: 99%
“…[41]. Wang et al demonstrated that concentrations of 1.8 mM and 3.8 mM Mg 2+ signi cantly decreased calcium oscillation amplitude or frequency, while increasing the concentration of Mg 2+ from 0.8 to 1.3 mM exhibited no effect on calcium oscillation frequency [42]. The authors deduced that a high Mg 2+ environment inhibits matrix mineralization by suppressing the calcium oscillation frequency in hBMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…[ 41 ]. Wang et al demonstrated that concentrations of 1.8 mM and 3.8 mM Mg 2+ significantly decreased calcium oscillation amplitude or frequency, while increasing the concentration of Mg 2+ from 0.8 to 1.3 mM exhibited no effect on calcium oscillation frequency [ 42 ]. The authors deduced that a high Mg 2+ environment inhibits matrix mineralization by suppressing the calcium oscillation frequency in hBMSCs.…”
Section: Discussionmentioning
confidence: 99%